2015
DOI: 10.1515/prolas-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Variation of Barley Characteristics and the Potential of Local Origin Genotypes for Food Production

Abstract: The aim of this study was to evaluate the genetic and environmental variation of yield and food quality characteristics (protein, starch, β-glucan and husk content, test weight and thousand grain weight) of covered and hulless barley genotypes in organic management conditions. Two different field experiments were carried out. In the first experiment, hulless barley genotypes 'Kornelija', 'Irbe', '1165', '1185' and the covered varieties 'Ansis' and 'Maali' were studied in two locations in Latvia and in one loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…The overall composition of barley is affected by genotypes, growing environment (Fox et al, 2007). Tamm, Jansone, Zute, and Jakobsone (2015) revealed that nitrogen supply, maturation date, yield affect the quality traits like protein, carbohydrate, and β‐glucan of barley.…”
Section: Resultsmentioning
confidence: 99%
“…The overall composition of barley is affected by genotypes, growing environment (Fox et al, 2007). Tamm, Jansone, Zute, and Jakobsone (2015) revealed that nitrogen supply, maturation date, yield affect the quality traits like protein, carbohydrate, and β‐glucan of barley.…”
Section: Resultsmentioning
confidence: 99%
“…The American standard for winter cereals is at least 74% of de-hulled grains. However, this standard may vary according to cereal use, year, climate conditions, and cultural habits (Tamm et al, 2015). According to this American standard, only hull-less barley would be well accepted in food industries.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, when considering the environment and genotype, it is also possible to identify an additional effect: the interaction between them. The influence of the environment demonstrates that cultivars developed differently in different locations, and that genetic factors are not the only factors that determine grain characteristics (Tamm et al, 2015). To better demonstrate the influence of the environment in the same cultivar, results from barley varieties that were cropped in two different areas are compared in Table 4.…”
Section: /8mentioning
confidence: 99%
See 1 more Smart Citation
“…The information about already achieved level of manifestation of yield-related traits in previously developed varieties has the practical worth for the purpose of consistent improvement of new varieties (Mirosavljević et al, 2016). The problem is that phenotypic manifestation of yield structural elements is largely determined by environmental conditions (Tamm et al, 2015). It is important for the breeder to have information about the genetically determined proportion in the overall phenotypic variability of yield structural components.…”
Section: Introductionmentioning
confidence: 99%